Cyclic AMP-Dependent Regulation of Kv7 Voltage-Gated Potassium Channels - van der Horst, Jennifer; Greenwood, Iain A.; Jepps, Thomas A. (Frontiers in Physiology, 2020)
Voltage-gated Kv7 potassium channels, encoded by KCNQ genes, have major physiological impacts in many cell types, such as cardiac myocytes, neurons, epithelial cells, and smooth muscle cells. Cyclic adenosine monophosphate (cAMP), a well-known intracellular secondary messenger, can activate numerous downstream effector proteins, generating downstream signaling pathways that regulate many functions in cells. A role for cAMP in ion channel regulation has now been established, and recent findings show that cAMP signaling plays a role in Kv7 channel regulation. Although cAMP signaling is recognized to regulate Kv7 channels, the precise molecular mechanism behind the cAMP-dependent regulation of Kv7 channels is complex. This review will summarize recent research findings that support the mechanisms of cAMP-dependent regulation of Kv7 channels.